Comparative Advantage Analysis of Trade between the Lao PDR and Countries in the Greater Mekong Sub-region - xiong, chue; Siphanthong, Bounthavy; Sengdala, Chansamone (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This study aims to: 1) analyze the trade situation between Lao PDR and the countries in the Mekong Subregion (GMS) and 2) evaluate the comparative advantage in trade using Vollrath's Relative Trade Advantage (RTA) index during the period 2020-2024. Using annual geographic data collected from Lao Trade Portal and ITC Trade Map at Level 2 product level and analyzed with descriptive statistics combined with RTA calculation for the main product categories with the highest total trade value of the top 5 of each trading partner. The analysis results indicate that: the total trade value of Lao PDR with the sub-region below the Mekong River in the period 2020-2024 has a continuous increasing trend and there is a high concentration in the 3 main trading partners: Thailand, China and Vietnam. The export structure still focuses on resource-based goods and primary goods, while the import of industrial goods or capital goods also indicates that: Overall, Lao PDR is in a surplus state, but the growth rate of the overall trade balance has a declining trend. The RTA found that Lao PDR has advantages in energy products, agricultural products and some groups of minerals, but has disadvantages in some types of products that reflect limitations in standards, transformation and competitiveness.